Investigating The Challenges In The Practice Of Multimodal Interpretation For Persons With Articulatory- Auditory- Visual Impairments In The Domain Of Healthcare In Cameroon - Christopher Che AZIBO, Lum Suzanne AYONGHE & Suh Joseph CHE (Akofena)
Abstract: In Cameroon, effective healthcare delivery is essential for individuals with articulatory, auditory, and visual impairments, yet these patients often face significant Communication barriers when faced with healthcare consultations. This study investigates the challenges in the practice of multimodal interpretation within healthcare settings, aiming to identify specific obstacles that hinder effective communication and patient care. Utilizing a mixed-methods approach, observations were carried out, interviews were conducted, questionnaires served to concerned persons and healthcare professionals and patients across various facilities. The findings reveal that inadequate training for healthcare providers, lack of resources, and cultural attitudes significantly impede the implementation of multimodal strategies. Additionally, we identified gaps in awareness and accessibility that further complicate communication efforts. These results underscore the urgent need for tailored training programs and resource allocation to enhance the effectiveness of multimodal interpretation in Cameroon’s healthcare system. By addressing these challenges, improvements would be recorded in health outcomes while fostering a more inclusive environment for individuals with sensory impairments. Keywords: Interpretation, Visual Impairment, Articulatory Impairment, Auditory Impairment, Healthcare